Research of Torsional Vibration Frequency Response Test Technology of RV Reducer - Jing Tan; Song Wang; Dishan Huang; Jingjun Gu; Ming Li; Qingyue Wei (Jixie chuandong)
The torsional vibration frequency response test method of RV reducer under torque excitation is introduced. RV reducer is a closed two-stage drive system， the first stage involute gear drive （input shaft） and the second stage cycloid-pin gear drive （output shaft） are respectively applied with white noise and sweep frequency excitation method， and the excitation and response signals are picked up to obtain the torsional vibration frequency response of RV reducer. The two existing methods for testing the frequency response of torsional vibration are compared and analyzed， the difference in frequency response between the two methods is pointed out， and the difference in natural frequency， damping rate estimation and response distribution is verified by actual torsional vibration experiment of RV reducer. The correctness of the test method is confirmed by the results. The research has certain reference value to the testing technology of torsional vibration frequency response of RV reducer.